An introduction to modern astrophysics - Carroll, Bradley W.; Ostlie, Dale A. (Pearson/Addison Wesley, 2007)
"An Introduction to Modern Astrophysics, Second Edition has been thoroughly revised to reflect the dramatic changes and advancements in astrophysics that have occurred over the past decade. The Second Edition of this market-leading book has been updated to include the latest results from relevant fields of astrophysics and advances in our theoretical understanding of astrophysical phenomena